Estratégias para o mercado de varejo com foco em clientes de baixa renda - Filgueiras, João Luis Melo (2011)
Starting from a case study conducted at Zezão Supermarket we seek to identify the retail strategies that must be adopted to achieve the low-income clients. With the Real Plan, the stabilization of Brazilian economy and the social programs developed by the Lula government many people entered the consumer market in the last decade. How retailers should act to attract this clientele, which preferences and mechanisms lead them to choose which establishments carry your shopping? Using the strategic dimensions of business expertise, brand differentiation, channel selection, product quality, technological leadership, service, pricing and leverages, proposed by Porter (2005) A search was performed with a sample of consumers, administrators and the owner of the supermarket to answer these questions. For consumers, the method of interview was closed and for owner managers it was open interviews, and direct observation by the researcher. The company's choice to be studied was Zezão Supermarket, seen to be recognized as a successful case of sales, also being a neighborhood grocery store that caters predominantly this consumer. Research results showed that low-income consumers are betting on good service, coupled with a wide variety of products, caring for the quality products they offer and for more affordable prices. We conclude that the adopted strategies are based on the constant preoccupation with customers, offering facilities such as sales at home by phone, picking up and dropping clients at their homes, air-conditioning and sound in the store, parking compatible with the frequency of clients, a spacious and airy store. It also provides training to employees and monitors how they conduct their behavior with clients. Strategies also offer a wide variety of products, most first-line, go through the union with other supermarkets seeking to cut costs, which together with the decrease in unit margin for profit and offering constant promotions provides the offer of affordable prices and terminates with the use of an information technology support and capacity fast enough to meet the expected demand. Another important conclusion of the dissertation was which of the schools of strategy, according to the classification of Mintzberg, Ahlstrand and Lampel (2007) would have more to do with the practices adopted by the supermarket, in the case, it was the entrepreneurship school. It also concluded that the affinity and harmony among customers, managers and even the owner and suppliers are also critical to success in serving the lower classes.